COVID-19 in Cirrhotic Patients: Is Portal Vein Thrombosis a Potential Complication? - Alshymaa A Hassnine; Amr M Elsayed (Canadian Journal of Gastroenterology and Hepatology)
Introduction. Several studies have demonstrated that thromboembolic events increased in patients with coronavirus infection, usually occurring in elderly patients with severe illness, associated with comorbid diseases such as diabetes and hypertension. Portal vein thrombosis (PVT) is a rare venous thromboembolic disease occurring typically in patients with an underlying disease such as decompensated cirrhosis with or without hepatocellular carcinoma (HCC). Aim. To evaluate incidence of occurrence of acute PVT in cirrhotic patients infected with 2019 coronavirus disease (COVID-19). Methods. This cross-sectional, observational study involved 70 patients of the liver cirrhosis: (group A) 28 patients with liver cirrhosis infected with COVID-19, and 42 patients with liver cirrhosis as the control group matched for age and sex (group B). All patients were subjected to thorough medical history, routine investigations (complete blood count, liver, and renal function tests), imaging in the form of abdominal and Doppler ultrasonography to assess the presence of acute PVT, serum ferritin, D-dimer, C-reactive protein, and PCR of COVID-19 for group A only. Results. There was a significant difference between the two groups regarding Doppler ultrasound findings as 3 of the patients in group A had PVT (10.7%), 2 of them had HCC diagnosed by triphasic CT abdomen, and only 1 patient in group B had PVT (2.3%) p<0.05. Conclusion. In cirrhotic patients infected with COVID-19, portal vein thrombosis may be a potential complication even in the absence of hepatocellular carcinoma; further prospective studies with longer follow-up may be needed.